1963
DOI: 10.1530/acta.0.0420293
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo-Neurohypophysial Neurosecretion After the Extirpation of Various Endocrine Glands

Abstract: The possible role of the hypothalamo-neurohypophysial system in regulating the release of the anterior pituitary hormones was studied in the rabbit and the rat. Thyroidectomy, gonadectomy and uni- and bilateral adrenalectomy were the experimental conditions used. The neurosecretory material (N. S. M.) was demonstrated by the aldehyde-fuchsin (AF) technique. Distinct differences were not seen in the different groups of rabbits on account of the great variation between individuals. In the rats, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These findings are in agreement with the observations of Brodish and Long, who found elevated corticotropinreleasing activity in the peripheral blood of hypophysectomized-adrenalectomized rats (11). Using a different approach, Arko et al (12) have reported an increase in the number of neurohypophysial nerve fibers terminating in the portal vessels of the median eminence two and a half weeks after adrenalectomy-they interpret this as a sign of increased transport of the neurosecretory material into the portal vessels. Although the identity of this neurosecretory material has not yet been established, Rinne (13) believes it might have a role in regulating the release of ACTH.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with the observations of Brodish and Long, who found elevated corticotropinreleasing activity in the peripheral blood of hypophysectomized-adrenalectomized rats (11). Using a different approach, Arko et al (12) have reported an increase in the number of neurohypophysial nerve fibers terminating in the portal vessels of the median eminence two and a half weeks after adrenalectomy-they interpret this as a sign of increased transport of the neurosecretory material into the portal vessels. Although the identity of this neurosecretory material has not yet been established, Rinne (13) believes it might have a role in regulating the release of ACTH.…”
Section: Discussionsupporting
confidence: 91%
“…That the neurosecretory fibers originating in or run ning through the PVN and ending in the external zone of the median eminence may have a role in regulating the pituitary-adrenal axis has already been suggested on the basis of morphological investigations. So-called Gomoripositive 'CRF granules' in the external layer of the median eminence accumulated following adrenalectomy and de creased after dexamethasone treatment [2,3]. Such fibers show positive immunocytochemical reaction with neurophysine and vasopressin antibodies and originate mainly from the paraventricular nuclei [4, 39.…”
Section: Discussionmentioning
confidence: 99%
“…T h at the la tte r blockade could be overcome only by electrical stim ulation of the preoptic region of the hypothalam us argues in favour of an effect at the level of the central nervous system (Quinn 1965). An effect bearing on the hypothalam us in shown also by the finding th a t in the mouse di phenylhydantoin interferes w ith the liypothalam o-hypophysial neuro secretory system (Kivalo et al 1958) and this system m ay have a role in the regulation of ACTH release (see R inne 1960, 1965, Arko et al 1963, R inne and Sonninen 1964. I t is possible th a t diphenylhydantoin affects the hypothalam ic centres, which participate in the neuro hum oral control of the anterior p itu itary gland by lowering their activity in the same way as it reduces the excitability of the nerve tissue in general, possibly by way of Na turnover (see Sparberg 1963).…”
Section: Discussionmentioning
confidence: 99%